Künstlers in paradise - Schine, Cathleen (Henry Holt and Company, 2023)
"There was a time when the family Künstler lived in the fairy-tale city of Vienna. Circumstances transformed that fairy tale into a nightmare, and in 1939 the Künstlers found their way out of Vienna and into a new fairy tale: Los Angeles, California, United States of America. An ill-timed visit forces twentysomething New Yorker Julian to shelter in place in Venice Beach with his glamorous and eccentric ninety-three-year-old grandmother, Mamie Künstler, and her inscrutable housekeeper. To pass the time, Mamie regales Julian with stories of her adolescent adventures among the émigré elite, from tennis lessons with Arnold Schoenberg to a romance with Greta Garbo. During his unexpected extended stay in his grandmother's crumbling domain, Julian undergoes his own personal quest as he reckons with the trajectory of the life he thought he wanted and what role he will choose to play in it all"--